PERTUMBUHAN DAN KADAR ARTEMISININ CINA BARU(Artemisia Vulgaris L). PADA INTENSITAS CAHAYA DAN KOMPOSISI MEDIA TANAM YANG BERBEDA - Ivo Octaviani; Zozy Aneloi Noli; Suwirmen Suwirmen (Biocelebes, 2016)
The is about the growth and artemisinin content of the Cina Baru (Artemisia vulgaris L.) in different light intensity and growth media composition. It conducted in the Center of Plant Nursery of Andalas University, Padang from March to April 2015. The study used split plot design with 4 treatments and 3 replications, as the main plot was according to the percentage of shading where devided into shading 0% (a0), shading 55% (a1), shading 65% (a2), shading 75% (a3) while sub plot was determined by the  growth media composition: 0 ton/ha (b0), 5 ton/ha (b1), 10 ton/ha (b2), 15 ton/ha (b3). The result showed that light intensity had effect on root growth and number of leaf, while fertilizer significantly influenced the number of leaves, wet weight, net weight. Fertilizer did not significantly have effect on the height of plant and was not able of increase the level of artemisinin, however indicated a strong correlation between net weight and artemisinin level of Artemisia vulgaris L. Keywords: Artemisinin levels, Fertilizer, Light Intensity, Shading